Studi Metaanalisis terhadap Intensitas Terapi Pada Pemulihan Bahasa Afasia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
It has been speculated that conflicting results demonstrated across poststroke or brain damage aphasia therapy studies might be related to differences in intensity of therapy provided across studies. This study provides a meta analitic review of the role intensity of aphasia therapy on aphasia recovery when thefindings aggregatedacrossstudies. The aim of the study is to investigate the relationship between intensity of aphasia therapy and aphasia recovery. It was found that after sampling error correction was r=O.201. These finding indicates that intensity of therapy aphasia have roles in recovery. Changes in mean scoresfrom each study were recorded. Intensity of therapy was recorded in terms of length of therapy and hours of therapy provided per week. This study conclusion intense therapy over a short amount of time can improve outcomes of speech and language therapy for aphasia.